Smart School Community: Inovasi Layanan Katering, Kantin, Laundry, dan Abudemen Berbasis Aplikasi - Pigo Nauli; Muhammad Ikhsan; Ninuk Dewi K (Universitas 45 Surabaya, 2025)
Schools, as part of the educational ecosystem, play an important role in building economic and social sustainability within their environment. However, many non-academic services in schools are still managed manually, such as student katering, laundry, school transport, and minimarkets. This community service activity aims to develop and assist the use of a web- and Android-based Supply Chain Management (SCM) Information System at SDIT Permata Bunda 2 under the Daarul Hikmah Foundation. The system is designed to integrate all non-academic school services by involving local SMEs, parents, and teachers. The implementation method includes needs analysis, system design, application training, and technical assistance. The results show that the training improved partners’ understanding of digital SCM concepts and application usage. Currently, the system is in the development and testing stage for feature improvement. The implementation of this SCM system is expected to improve service efficiency, strengthen stakeholder collaboration, and support the school’s sustainability program.